2013
DOI: 10.1002/bsl.2077
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Culture and Language in Avoiding Misinformation: Pilot Findings

Abstract: In two pilot studies, we investigate the possibility that patterns in our linguistic environment affect the likelihood of accepting misinformation. Turkish, which marks its verbs for the source of a speaker's evidence (first-hand perception vs. hearsay), was contrasted with English which does not mark its verbs but which, to signal strength of evidence, must employ optional lexical marking. In the first pilot study, Turkish adults were shown to be affected by that language's obligatory evidential markings: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In one study, adult Turkish speakers were found to be less accurate in recognizing the information reported in non‐first‐hand form (as indicated by indirect evidential marking, ‐ mIş ) compared to information reported in first‐hand form (as indicated by direct evidential marking, ‐ dI ; Tosun, Vaid, & Geraci, ). In another study, Turkish‐speaking adults were less prone to suggestibility to misinformation when the original information was marked by the direct evidential and the misleading information was marked by the indirect evidential compared to the opposite situation (i.e., when the original information was marked by the indirect evidential and the misleading information was marked by the direct evidential; Aydın & Ceci, ). These results suggest that explicit choices about the evidential forms included in linguistic messages have further cognitive implications about how information is remembered.…”
Section: Cross‐linguistic Diversity and Source Monitoringmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study, adult Turkish speakers were found to be less accurate in recognizing the information reported in non‐first‐hand form (as indicated by indirect evidential marking, ‐ mIş ) compared to information reported in first‐hand form (as indicated by direct evidential marking, ‐ dI ; Tosun, Vaid, & Geraci, ). In another study, Turkish‐speaking adults were less prone to suggestibility to misinformation when the original information was marked by the direct evidential and the misleading information was marked by the indirect evidential compared to the opposite situation (i.e., when the original information was marked by the indirect evidential and the misleading information was marked by the direct evidential; Aydın & Ceci, ). These results suggest that explicit choices about the evidential forms included in linguistic messages have further cognitive implications about how information is remembered.…”
Section: Cross‐linguistic Diversity and Source Monitoringmentioning
confidence: 97%
“…In other words, do cross‐linguistic differences in the encoding of evidentiality influence performance even when speakers are not required to process evidential language while performing a task? Both adult and developmental studies have shown that linguistic categories of evidentiality have cognitive consequences, but that these linguistic influences are strictly limited to cases where language was explicitly involved in a cognitive task (e.g., contexts in which people had to process sentences with evidential markers; Aydın & Ceci, ; Tosun et al., ). When speakers were tested with cognitive tasks that did not require processing linguistic stimuli, no cross‐linguistic differences emerged (Papafragou, Cassidy, et al., 2007; Papafragou, Li, et al., 2007; Ünal et al., ).…”
Section: Summary and Prospectusmentioning
confidence: 99%
“…In particular, in both types of language people tended to present indirectly acquired information as directly acquired information. However, the work conducted so far has focused either on young children (preschoolers: Aydin & Ceci, 2013;Papafragou et al, 2007), or on tasks putting significant strain on memory (such as remembering dozens of new pictures: Ünal et al, 2016). As a result, the source flexibility exhibited in these studies might have been the result of cognitive constraints, rather than of social motivation.…”
Section: Evidentiality and Flexibility In Source Reportingmentioning
confidence: 99%
“…When bilinguals are concerned, it also means that encoding can be different depending on the language they use at the moment. Yet, while episodic and autobiographical memory in bilinguals has been widely researched and differences in encoding and retrieval processes were observed (Boroditsky et al, 2009 ; Fausey and Boroditsky, 2011 ; Aydin and Ceci, 2013 ), there have been only a handful of studies investigating the suggestibility in bilinguals (Shaw et al, 1997 ; Smith et al, 2017 ; Calvillo and Mills, 2020 ). Although misinformation effect was present in all these cross-linguistic studies, the results regarding the influence of the language on the endorsement of false information show inconsistent findings, reporting no significant differences between the conditions (Shaw et al, 1997 ) or explaining the results in relation to the different levels of proficiency between the languages (Calvillo and Mills, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Observed cross-linguistic differences in memory performance were described as caused by the different grammar patterns specific to these languages, e.g., more frequent use of an agent in the English language compared to Japanese or Spanish. Similar studies also explored the effect in several other languages, including Turkish (Aydin and Ceci, 2013) and Indonesian (Fausey and Boroditsky, 2011), as well as different linguistic characteristics, such as the usage of definite or indefinite articles (Loftus, 1975), grammar tenses (Boroditsky et al, 2019), or gender (Boroditsky et al, 2003), all showing variations in the memory performance attributed to the specific linguistic characteristics.…”
Section: Introductionmentioning
confidence: 99%